Kualitas Tidur Buruk Memperlambat Waktu Reaksi Visual pada Mahasiswa Program Studi Sarjana Fisioterapi Fakultas Kedokteran Universitas Udayana - Hafizh Marin; Agung Wiwiek Indrayani; Made Hendra Satria Nugraha; I Made Krisna Dinata (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: College students are one of the groups that have a high risk of experiencing sleep deprivation and sleep disorders. In medical students, this is due to the high duration and intensity of education. Poor sleep quality causes impaired cognitive function, one of which is decreased reaction time. Students with faster reaction times have better cognitive status and academic performance. This study aims to determine how the relationship of sleep quality to reaction time with the type of simple reaction time (SRT) and choice reaction time (CRT) experiment in physiotherapy student at faculty of medicine, university of udayana.Methods: The cross-sectional study was conducted with simple random sampling technique. 45 students participated in this study. Sleep quality was measured with Pittsburgh Sleep Quality Index (PSQI) and reaction time using Deary-Liewald reaction time task with SRT and CRT types of experiment. Bivariate analysis was performed using the Spearman rho test.Result: 21 people (46.7%) had good sleep quality and 24 people (53.3%) had poor sleep quality. The results showed that there was a relationship between sleep quality and reaction time using CRT (p = 0.003) and there was no relationship between sleep quality and reaction time using SRT (p = 0.084).Conclusion: Poor sleep quality resulted in decreased reaction time with the CRT experiment type. The authors suggests research with different methods and populations, also add more control variables.